POST-STROKE USE OF PIOGLITAZONE IMPROVES ATHEROTHROMBOTIC HEMISPHERIC STROKE OUTOME IN NON-DIABETIC ABDOMINALLY OBESE PATIENTS - Delva M.І. (World of Medicine and Biology, 2013)
The aim of this study was to determine if abdominally obese patients taking pioglitazone after hospital admission for ischemic atherothrombotic hemispheric stroke had an improved clinical outcome. This prospective study evaluated 63 non-diabetic abdominally obese patients (class II obesity) aged 67.9±0.7 years (43% women) with acute ischemic atherothrombotic hemispheric stroke. Patients were matched for National Institutes of Health Stroke Scale score at admission, cerebral infarcts volume and pre-stroke disability. Patients were randomized into a control group (n=32) and a pioglitazone 30 mg/d group (n=31). Treatment with pioglitazone was initiated within 72 hours after the onset of stroke and continued up to 12 weeks. Favorable outcome was defined as modified Rankin scale (mRS) score ≤2 and Barthel index (BI) ≥85 at discharge, at 4 and 12 weeks. There was no any difference in functional outcomes at discharge. According to mRS, late favorable outcomes were more frequent in the pioglitazone group (OR 3.70; 95% CI 1.26 to 10.13; p=0.028 at 4 week; OR 3.68; 95% CI 1.18 to 10.60; p=0.04 at 12 week). Similar findings were observed with BI (OR 3.89; 95% CI 1.29 to 10.85; p=0.025 at 4 week; OR 4.04; 95% CI 1.22 to 12.11; p=0.03 at 12 week). Post-stroke use of pioglitazone is associated with improved late outcome in abdominally obese patients with acute atherothrombotic hemispheric stroke.